Identification of a defective molecule derived from DNAA of the bipartite begomovirus of East African Cassava Mosaic Virus - Ndunguru, J.; Legg, James P.; Fofana, B.; Aveling, T.; Thompson, G.; Fauquet, Claude M. (Wiley, 2006)
Geminivirus defective interfering DNAs arise spontaneously in mechanically inoculated test plants, and have previously been found with DNA‐B of the bipartite cassava mosaic geminiviruses, but not DNA‐A. Reported here for the first time is the cloning and characterization of a naturally occurring truncated form of cassava mosaic geminivirus DNA‐A, which at 1525 nt is around half the expected full size. Sequence analysis has shown it to be a defective (df) form of East African cassava mosaic virus (EACMV) DNA‐A that has retained its cis elements essential for replication by the helper virus, and it has been termed df DNA‐A 15. Phylogenetic comparisons placed the df DNA‐A 15 molecule close to mild and severe isolates of EACMV‐UG2. Biolistic inoculation of Nicotiana benthamiana with infectious df DNA‐A 15 clone and East African cassava mosaic Cameroon virus (EACMCV) resulted in symptom amelioration as compared with EACMCV singly inoculated plants, and there was an accumulation of df DNA‐A 15 in systemically infected leaves. In addition, the level of EACMV DNA‐B accumulation was reduced in the coinoculated plants compared with those inoculated with EACMCV alone. PCR and sequence analysis confirmed the helper virus as EACMV.